Automation in volume fraction of binary phase components. Issue 1 (31st December 2022) - Ashraf Ali, M.; Mohamed Ismail, A.
Abstract : The automation in volume fraction of binary phase components finds a vital role in many chemical and open channel flow passages. In this experimental work, the dissolved air sensor is employed to determine the volume of air in water automatically. The air water mixture is subjected to uniform flow conditions and the air is made to penetrate in water at different elevations and the percentage volume of air is measured. This paper describes the experimental method to measure the volume of air in water and the corresponding results are highlighted.